Pendidikan Anti Kekerasan Seksual dalam Mengeskalasi Hukum Berkeadilan Bagi Generasi Muda Desa Gogik Kabupaten Ungaran Barat - Tutik Wijayanti; Iwan Hardi Saputro; Hafiz Rafi Uddin; Yudha Pratama Widiyanto; Siti Fatimah; Bagus Darmawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Acts of sexual violence have now become a crucial issue regarding the moral decline in society. Sexual violence is a situation where a person experiences harassment in the form of inappropriate words and physical contact without mutual consent, resulting in discomfort for the victim.In fact, Article 28B Paragraph 2 of the 1945 Constitution states, 'Every child has the right to survive, grow, and develop, and has the right to protection from violence and discrimination.' However, in reality, many communities that still uphold patriarchal values often offer socially manipulative solutions, such as asking the victim to marry the perpetrator. Reflecting on this article, every human being has the right to be protected from acts of violence. However, the widespread sexual crimes against teenagers and the failure and injustice in handling such cases have become serious issues. Motivated by the spirit to prevent and address the problem of sexual violence, the service team implements sexual violence prevention education for the younger generation. This program is a child-friendly initiative that not only addresses sexual crimes but also serves as an educational platform. It is not limited to handling victims but also aims to break the vicious cycle involving teenagers as perpetrators of sexual violence. Therefore, this program is expected to answer, assist, and raise public awareness about the critical issue of sexual crimes in Indonesia.